Effects of Work-Life Balance and Job Burnout Towards Job Satisfaction - Wulantika, Lita; Atifah, Ratu Nadya (Faculty of Economics and Business, Universitas Klabat, 2024)
This study aimed to examine the influence of Work-Life Balance and Job Burnout on Job Satisfaction among employees of PT. Eternal Sunrise in Bandung City using a quantitative method. The population consisted of 65 employees of PT. Eternal Sunrise, and the sample size included all members of the population, using saturated sampling. Data collection techniques included interviews, literature studies, and questionnaires, analyzed with Multiple Regression Analysis. Data processing was conducted using SPSS 27. The research results showed that Work-Life Balance had a significant impact on Job Satisfaction among PT. Eternal Sunrise employees. Similarly, Job Burnout also had a significant impact on Job Satisfaction. Simultaneously, Work-Life Balance and Job Burnout significantly influenced Job Satisfaction among PT. Eternal Sunrise employees.